Prevalence and Predictors of Cerebral Microangiopathy Determined by Pulsatility Index in an Asymptomatic Population From the ILERVAS Project - Purroy, Francisco; Sánchez, Enric; Lecube, Albert; Arqué, Gloria; Vicente-Pascual, Mikel; Mauri-Capdevila, Gerard; Torreguitart, Núria; Hernández, Marta; Barbé, Ferrán; Fernández, Elvira; Pamplona, Reinald; Farràs, Cristina; et al. (Frontiers in Neurology, 2021)
Background: Little is known about the prevalence of cerebral microangiopathy (CM), which is related to cognitive impairment, in an asymptomatic population. Pulsatility index (PI) is an easily measurable parameter of cerebral vascular resistance in transcranial duplex of the middle cerebral artery (MCA) study. We aimed to determine the prevalence of CM measured by PI of MCA in low to moderate vascular risk subjects. Methods: We included 3,721 subjects between 45 and 70 years without previous history of vascular disease or diabetes mellitus and with at least one other vascular risk factor from the cross-sectional study ILERVAS (Lleida, Spain). Patients underwent transcranial duplex to determine MCA-PI. Possible CM was defined by MCA-PI >1.1. Carotid and femoral arteries ultrasound registration was done to determine the presence, the number, and the area of atheromatous plaques. Body mass index (BMI), pulse pressure (PP) and laboratory data were also recorded. Results: 439 (11.8%) subjects were excluded due to the low quality of transcranial duplex images. Median age was 57 [IQR 52, 62] years. Possible CM was found in 424 (12.9%) subjects. CM patients had higher prevalence of plaques than non-CM (77.4 vs. 66.4%, p < 0.001). PI showed a positive linear correlation with the number of territories with plaques (r = 0.130, p < 0.001), and the total plaque area (r = 0.082, p < 0.001). The predictors of possible CM were the age, male gender, and PP. Conclusions: In low-to-moderate vascular risk asymptomatic population, the proportion of abnormal brain microvascular bed determined by MCA-PI is not negligible. The planned 10-year follow-up will describe the clinical relevance of these findings.